PEMANFAATAN LIMBAH BUDIDAYA IKAN LELE (Clarias batrachus) UNTUK IKAN NILA (Oreochromis niloticus) DENGAN SISTEM RESIRKULASI - Lies Setijaningsih; L.H. Suryaningrum (BERITA BIOLOGI, 2015)
The effluent generated from aquaculture can be exploited through the application of aquaponics technology. The aim of this research was to evaluate the utilization of catfish culture waste by tilapia based on closed recirculation. Catfish and tilapia were used as fish test while water spinach was used as a biofiltration. Dissolved of nitrogen and phosphorus that obtained from catfish culture would be utilized by water spinach. Completedly Randomize Design with consisted of three treatments and three replicates were performed. The different stocked density on catfish culture were used as a treatment i.e. 500 individuals per pond (P1); 1000 individuals per pond (P2); and 1500 individuals per pond (P3). Different stocking density was also applied to tilapia culture as a treatment namely 50 individuals per m2 (Q1); 100 individuals per m2 (Q2); and 150 individuals per m2 (Q3). Result showed that catfish culture with stocking density of 1500 individuals per pond (P3) was better than (P1) and (P2) in terms of absolute weight growth, specific growth rate, and survival (P<0.05). Absolute weight growth, specific growth rate, and survival of tilapia cultured at Q2 (stocking density of 100 individuals per m2) and Q3 (stocking density of 150 per m2) were better than Q1 (stocking density of 50 individuals per m2) (P<0.05).